Scheme of mobile informatization in electric power enterprise - Hualu ZHANG; Wei JIA; Tianbing ZHANG; Zhongran ZHOU (Dianxin kexue)
The electric power enterprises' mobile information development trend was analyzed,an enterprises' mobile informatization scheme based on enterprise “mobile platform and mobile applications”was put forward,including the overall technical route and the overall architecture,the design of enterprise's unified mobile internet application support platform,the construction scheme of mobile application based on the mobile platform and the safety design of mobile informatization implementation.At present,the scheme has been successfully applied in the state grid corporation.